Optimization of the culture medium composition using response surface methodology for new recombinant cyprosin B production in bioreactor for cheese production - Sampaio, Pedro N. (2011)
The optimization of culture medium compositionwas carried out for improvement the recombinantcyprosin B production, an enzyme with high milk-clottingactivity. Response surface methodology (RSM) wasapplied to evaluate the effect of variables namely glucose,yeast extract (YE) and bactopeptone present in the culturemedium, used for recombinant cyprosin B production bytransformed Saccharomyces cerevisiae BJ1991 strain inshake-flask and bioreactor culture conditions. The centracomposite experimental design (CCD) was adopted toderive a statistical model for optimizing the composition ofthe fermentation medium. The optimal concentration estimatedfor each variable related to a theoretical maximumof cyprosin B activity (488 U mL-1) was 30 g L-1 glucose,15 g L-1 YE and 27 g L-1 bactopeptone. The optimizedmedium composition, based on empirical model, ledto a cyprosin B activity of 519 U mL-1, which correspondsto an increase of 46%. The fermentation using optimizedculture medium in a 5-L bioreactor allowed a significantincrease in biomass (82%) and recombinant cyprosin Bproduction (139%). The improvement in the recombinantcyprosin B production after optimization process can beconsidered adequate for large-scale applications, and theclotting activity of cyprosin B account for their use inindustrial cheese making.